ANALISIS TINGKAT KESEHATAN BANK PERKREDITAN RAKYAT (BPR) DENGAN METODE CAMEL DI KOTA BATAM - Puspita Rama Nopiana; Mufidatul Mufidatul (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
ABSTRACT Bank an a financial institution that its role in supporting economic development in an area, which raised funds activities and disbursing funds in the form of loans or credit is a form of that money circulates to stabilize the economy. The purpose of this study was to conduct analysis of the banking healthy level on Bank Perkreditan Rakyat (BPR) in Batam City, for 2012-2016 periods. This research uses descriptive quantitative research design. The report data were extracted from bank’s financial from financial report which had been published by Otoritas Jasa Keuangan (OJK). The assessment analysis of banking healthy level has been carried out by using CAMEL method (Capital, Asset, Management, Earning, and Liquidity) which is based on the decree of BI director No.30/12/KEP/DIR on April 30th, 1997. The results showed that the healthy level of Bank Perkreditan Rakyat (BPR) in Batam City for 2012-2016 periods showed categorized healthy, where the value – average CAR ratio of 13.68%, KAP ratio of 1.76%, NPM ratio of 16.51%, ROA ratio of 3.86%, BOPO ratio 78.01%, and LDR ratio of 87.05%. Expected for the future later BPR could continue to keep even better, so the level of health can be guaranteed according to applicable regulations.